2021
DOI: 10.1007/s00709-021-01620-6
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological, morphological, and biochemical traits of free-living Diplosphaera chodatii (Trebouxiophyceae) reveal adaptation to harsh environmental conditions

Abstract: Single-celled green algae within the Trebouxiophyceae (Chlorophyta) are typical components of terrestrial habitats, which often exhibit harsh environmental conditions for these microorganisms. This study provides a detailed overview of the ecophysiological, biochemical, and ultrastructural traits of an alga living on tree bark. The alga was isolated from a cypress tree in the Botanical Garden of Innsbruck (Austria) and identified by morphology and molecular phylogeny as Diplosphaera chodatii. Transmission elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…However, the combination of sorbitol + sucrose may be consistent within the genera studied. A recent work by Medwed et al (2021) also shows that Diplosphaera produces sorbitol + sucrose during growth. These findings support the phylogenetic exclusion of the algal strain SAG 48.41 from the Stichococcus-like genera, as it does not produce sorbitol.…”
Section: Acknowledgementsmentioning
confidence: 88%
See 2 more Smart Citations
“…However, the combination of sorbitol + sucrose may be consistent within the genera studied. A recent work by Medwed et al (2021) also shows that Diplosphaera produces sorbitol + sucrose during growth. These findings support the phylogenetic exclusion of the algal strain SAG 48.41 from the Stichococcus-like genera, as it does not produce sorbitol.…”
Section: Acknowledgementsmentioning
confidence: 88%
“…The NMR spectra were recorded with a Bruker spectrometer ( 1 H: 500.13 MHz; 13 C: 125.8 MHz, AVANCE 500 Neo spectrometer (Bruker BioSpin, Ettlingen, Germany). Chemical shifts δ are given in ppm relative to the signal for internal est: the presence of low molecular weight carbohydrates (LMWC) has both consequences for the cell biology and physiology in terms of osmotic stress tolerance (Roberts 2005, Holzinger and Karsten 2013, Holzinger and Pichrtová 2016 and has been demonstrated to be a stable taxonomic character (Gustavs et al 2011, Darienko et al 2015, Hotter et al 2018. It also provides valuable information on the ecophysiology of the strains, which is usually missing from classical phylogenetic analyses.…”
Section: Qualitative and Quantitative Lmwc Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies in Trebouxiophyceaen algae present on tree bark showed that they, as one biofilm unit, are able to survive and recover after being exposed to extended drought periods of up to 80 days [35]. This was reiterated in [58], where a Diplosphaera chodatii isolate collected from tree bark reached nearly 100% initial Y(II) after being exposed to water for post-dehydration, albeit after a far shorter desiccation period (45 min at 10% RH).…”
Section: Dehydration and Rehydrationmentioning
confidence: 89%
“…It was not until beyond this time that there was an appreciable uptick overall. Medwed [58] and Karsten [32] showed recovery that reached a plateau at~190 and~1000 min, respectively, so it is possible that the Stichococcus-like strains needed slightly longer to reach peak recovery.…”
Section: Dehydration and Rehydrationmentioning
confidence: 99%